Engaging private providers to enhance tuberculosis detection and notification: evidence from TB REACH-Supported projects - Md. Toufiq Rahman; William A. Wells; Oriol Ramis; Vishnu V. Kamineni; Mirjam I. Bakker; Sode Matiku; Miranda Brouwer; Jacob Creswell (BMC Public Health)
Abstract Background Private providers (PPs), rather than public facilities, are often the first point of contact in the health system for people with tuberculosis (TB). However, PP’s potential for enhancing TB detection remains underutilized. Methods TB REACH is an initiative of Stop TB Partnership focused on improving TB detection and notification. We analyzed the results of interventions using private provider engagement (PPE) to impact TB detection and notification across four TB REACH funding waves from May 2018 through March 2022. Results Overall, 35 projects documented screening of 13,038,586 people for TB, referral of 384,364 (3% of those screened) for diagnostic testing, and testing of 332,266 (86%) people. In total, 64,456 all forms of TB were diagnosed, and 62,830 (97% of those diagnosed) were linked to treatment. To diagnose one person with TB, the overall number needed to screen and test was, respectively, 281 (range across projects: 2–8,705) and 7 (range across projects: 1–24). Twenty-five projects mapped 69,187 PPs, both formal and informal, and engaged 21,206 (31%) providers during the intervention period, 12,211 (58%) of whom actively referred at least one person with TB symptoms during the intervention period. During the implementation period, TB notifications in the intervention areas increased by 25% (n = 61,123; from 246,845 to 307,968), with 20% of the total TB notifications attributed to the PPE projects. The mean and median cost per person started on treatment through the PPE projects was USD 221 and USD 481 (range across projects: 23 − 8,689). Conclusions Our findings suggest that structured and targeted PPE enhances TB case finding and contribute in closing the gap of missing cases. These results emphasize the need for wider implementation and scale-up of PPE in the TB response.